Perlindungan Data Pribadi dalam Transaksi Digital: Implikasi Regulasi, Keamanan, dan Efisiensi dalam Perspektif Hukum Ekonomi dan Hukum Islam - Purnama Hidayah Harahap (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The rapid development of digital transactions poses new challenges in personal data protection, especially related to aspects of regulation, security, and efficiency. This article aims to analyze the implications of personal data protection in digital transactions from the perspective of economic law and Islamic law. Using a normative and empirical approach, this study explores the effectiveness of applicable regulations, the level of data security implemented by digital service providers, and their impact on economic efficiency in the digital ecosystem. The results of the study show that although regulations related to personal data protection, such as Law No. 27 of 2022 concerning Personal Data Protection (PDP), have been implemented, there are still various obstacles in their implementation, including weak law enforcement and low public awareness. From the perspective of economic law, effective protection of personal data can increase consumer trust and stability of the digital market, but on the other hand, the implementation of strict regulations can also create an economic burden for business actors. Meanwhile, from the perspective of Islamic law, the protection of personal data is in line with the principles of hifz al-'ird (protection of honor) and hifz al-mal (protection of property), which emphasize the importance of safeguarding individual rights and preventing the misuse of personal information. Thus, this study emphasizes the urgency of improving regulations and strengthening data security infrastructure to create a balance between privacy protection, legal certainty, and economic efficiency in digital transactions. In addition, the integration of Islamic legal values in personal data protection policies can be a more holistic approach in building a fair and sustainable data protection system.